2011
DOI: 10.1161/hypertensionaha.111.177501
|View full text |Cite
|
Sign up to set email alerts
|

Closer to Noninvasive Out-of-Office Aortic Blood Pressure Assessment

Abstract: See related article, pp 825-832T he noninvasive assessment of central (aortic or carotid) blood pressure (BP) is a challenge to the clinical investigation of arterial hypertension. The importance of central BP was recognized decades ago on the basis of invasive hemodynamic studies 1 but has become widely acknowledged during the last 15 years. 2 This is largely attributed to the work of highly respected pioneers, like Michael O'Rourke's team, who created the first commercial device (SphygmoCor, AtCor, Sydney, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
0
11
0
3
Order By: Relevance
“…First, Mobil-O-Graph records brachial BP and pulse waves using the oscillometric method; although this differs from the most widely applied technique of applanation tonometry (23), previous validation studies in different populations (including patients with ESRD) showed acceptable agreement between Mobil-O-Graph-derived variables and invasive and noninvasive measurements (23,24,28,30,31). Second, because this was a pilot study, no power estimation was performed before its initiation; we believe, however, that the number of participants, together with the high number of readings (.120) during the 48-hour recordings, provided adequate power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Mobil-O-Graph records brachial BP and pulse waves using the oscillometric method; although this differs from the most widely applied technique of applanation tonometry (23), previous validation studies in different populations (including patients with ESRD) showed acceptable agreement between Mobil-O-Graph-derived variables and invasive and noninvasive measurements (23,24,28,30,31). Second, because this was a pilot study, no power estimation was performed before its initiation; we believe, however, that the number of participants, together with the high number of readings (.120) during the 48-hour recordings, provided adequate power.…”
Section: Discussionmentioning
confidence: 99%
“…A newly introduced ABPM device (Mobil-O-Graph; IEM, Stolberg, Germany) records oscillometric BP and pulse waveforms at the brachial artery and provides valid measures of aortic BP, AIx, and PWV in ambulatory conditions (22)(23)(24). This study aimed to investigate for the first time the variation of central BP, AIx, and PWV during 48-hour ABPM in hemodialysis patients in order to compare differences in these indices between in-dialysis and out-of-dialysis periods and explore associations of demographic, clinical, and hemodynamic parameters with ambulatory AIx and PWV.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Our recent publication proved that, as compared with 24-h brachial AMBP, 24-h aortic ABPM is better associated with left ventricular hypertrophy. 12 The aim of the present analysis, within the context…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Our recent publication proved that, as compared with 24-h brachial AMBP, 24-h aortic ABPM is better associated with left ventricular hypertrophy. 12 The aim of the present analysis, within the context of the 'Non-invaSive Aortic ambulatory blood pressure monitoring For the detection of tARget organ damage (SAFAR)' study, was to investigate the hypothesis that LVDD is better associated with 24-h aortic BP, than office (brachial and aortic) BP and 24-h brachial BP.…”
Section: Introductionmentioning
confidence: 99%
“…A newly introduced brachial cuff-based oscillometric ABPM device (Mobil-O-Graph, IEM, Stolberg, Germany) records BP and pulse waveforms at the brachial artery and estimates aortic BP, augmentation index (AIx) and pulse wave velocity (PWV) in the ambulatory setting [15,16]. However, this device has major methodological differences from the currently applied tonometry-based methods, raising the issue of investigating its validity.…”
Section: Introductionmentioning
confidence: 99%